Determinan Perawatan Bayi Berat Lahir Rendah di Wilayah Pertanian dan Pesisir Berperspektif Keluarga - Ira Rahmawati; Rahmawati, Iis; Juliningrum, Peni Perdani; Merina, Nuning Dwi; Susanti, Ika Adelia; Alfurqon, Achmad Syarofi (LPPM Hang Tuah Pekanbaru, 2025)
Low birth weight babies (LBW) in agricultural and coastal areas have different health problems thus possibly having different care needs. Inappropriate promotion of child health, especially LBW, in both clinical and community service settings can increase morbidity and mortality rates. The purpose of this study was to identify the determinants of LBW babies care needs based on family perspectives in coastal and agricultural areas. This cross-sectional observational study was conducted in June 2023 using a questionnaire to identify the determinants of LBW’s babies care. The population of this study was children and mothers in coastal and agricultural areas. Multistage random cluster sampling with the G*Power application obtained 193 participants per region, resulting in a total sample of 386. Data were analyzed using difference in means between two regions. The results showed that agricultural regions had higher mean on LBW care, parental stress, and family empowerment. Coastal areas had higher mean scores on quality of life, maternal confidence, and food diversity practices. There was a significant difference between coastal and agricultural areas on the determinants of LBW’babies care between coastal and agricultural areas, especially on the variables of parental quality of life (p=0.000), parenting stress (p=0.029), maternal confidence (p-0.000) and family empowerment (p = 0.000). Optimizing health promotion by pediatric nurses in the scope of hospital and community settings can be achieved by empowering families and paying attention to parenting stress, maternal confidence, and parents' quality of life.